Proof Of Criminal Origin Related To Money Laundering In Mutual Fund Investment Activities In Supreme Court Decision Number 2937 K/Pid.Sus/2021 - Surnada, Surnada; Kusbianto, Kusbianto; Sitompul, Ariman (Legalpreneur Journal, 2024)
The crime of money laundering in the form of mutual fund investments is a serious crime that can threaten the stability of the financial system and economy. Perpetrators use mutual funds as a means to disguise the origin of illegal funds resulting from criminal acts, such as corruption, which are then invested as if they were legitimate funds. This not only harms the country financially, but can also reduce investor confidence in the mutual fund industry. Therefore, it is important to examine the criminal liability of perpetrators of money laundering in mutual fund investments in order to maintain the integrity of the financial system and provide a deterrent effect for perpetrators of similar crimes. This research is aimed at analyzing the legal regulation of criminal acts of money laundering in mutual fund investment activities in Indonesia, proof of predicate crimes related to criminal acts of money laundering in mutual fund investment activities in Supreme Court Decision Number 2937 K/Pid.Sus/2021, as well as criminal responsibility for perpetrators of these crimes. money laundering crime in mutual fund investment activities in Supreme Court Decision Number 2937 K/Pid.Sus/2021.The research method used is normative juridical research, which is supported by primary and secondary data sources. All legal materials were collected using library research techniques using document study data collection tools. Apart from that, field studies were also carried out using interview methods and analyzed qualitatively.The results of the research and discussion concluded that the legal regulations related to the crime of money laundering in mutual fund investment activities in Indonesia are as regulated in Law Number 8 of 2010. Based on Supreme Court Decision Number 2937 K/Pid.Sus/2021, it can be concluded that the defendant Benny Tjokrosaputro proven to have committed a criminal act of corruption together with other parties in managing investments at PT Asuransi Jiwasraya (Persero) which caused state losses amounting to IDR 16.807 trillion, as well as a money laundering crime of IDR 6.078 trillion, so he was sentenced to life imprisonment and payment of compensation to the state, based on valid evidence at trial and the fulfillment of the elements of the criminal act in accordance with the articles charged.